PERSEPSI PENGURUS NU DAN MUHAMMADIYAH KABUPATEN BANTUL TERHADAP PELAKSANAAN FUNGSI DPRD KABUPATEN BANTUL TAHUN 2008 - LESTARI, LINAYATI (POLITIK DAN KEBIJAKAN PUBLIK, 2014)
This paper is a description and analysis of the associated power and involvement of local communities in performing the functions of government control over the region. Representation in Parliament can be measured by the extent to which the community through representation functions performed parliament made such a legislative function, the function of oversight, and budgetary functions. From the research conducted it was found that the perception of NU administrators to legislators Bantul Year 2008 in the District Piyungan fit in either category, with 3.61 index scale. Perception Management of Muhammadiyah the Bantul legislators in 2008 in District Banguntapan fit in either category, with the index scale 3.59. Perception NU and Muhammadiyah organizations represented by the Council believes they Bantul.This is influenced by the level of communication between the representatives of the people with these organizations. Communication is done usually through the vertices aspirations of community leaders and organizations management itself, so that activist organizations are over-represented. There is no significant difference between the perceptions of administrators NU and Muhammadiyah. They assess Bantul parliament regarding the conduct of its functions (legislative, budgetary, oversight, representation) is in the good category.Parliament considered relatively good performance, the NU and Muhammadiyah Organizations must be able to appreciate it. So even though Parliament Bantul respondents categorized both NU and Muhammadiyah but still need to be critical, so there is some sort of control over both the legislative and executive government. In this paper the authors conclude that respondents form a perception of what they know, and natural. The authors expect the emergence of new research on public perception of the function of the legislature so that there is control of society.Keywords: Perception, Parliament functions, Nahdlatul Ulama, Muhammadiyah.